IMPLEMENTASI PELAYANAN PUBLIK DI KANTOR WILAYAH KEMENTERIAN HUKUM PROVINSI RIAU TAHUN 2024 - Mukminin, Amirul; Yusri, Ali (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
This study discusses the implementation of public services at the Regional Office of the Ministry of Law and Human Rights in Riau Province, which includes the availability, management, maintenance, and obstacles in providing legal services and correctional services. The conceptual framework of this research is built on the assumption that the quality of public services is not only determined by human resources and service systems, but is also strongly influenced by adequate, standardized, and supportive facilities and infrastructure for the needs of the community and service users. This research employs the Public Service Theory by Zeithaml, Parasuraman, and Berry (SERVQUAL) is used to measure service quality based on five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. The research method used in this study is qualitative descriptive, with data collected through interviews, observations, and documentation. The research informants consist of employees of the Regional Office of the Ministry of Law and Human Rights in Riau Province, related Technical Implementation Units, as well as service users. The results show that the implementation of public services from the aspect of managing facilities and infrastructure has been carried out but is not yet fully optimal. Facilities such as waiting rooms, elderly-friendly service access, technology-based service systems, and correctional facilities still face shortcomings, including damaged conditions, limited capacity, and the failure to fully meet public service standards across all units. Improvement efforts have been made in the form of procuring priority facilities, basic facility maintenance, gradual budget adjustments, and the use of digital service technologies. Keywords: Public service, policy implementation, facilities and infrastructure, Regional Office of the Ministry of Law and Human Rights Riau.